International Buisness English (video). Teachers Guide. - Jones, Leo (Cambridge Cambridge University Press, 1993)
The International Business English Video contains three dramatized business stories, two documentaries and two sequences of interviews with professionals about their day-to-day working lives.
Keywords: Business English